E-cadherin Plays a Role in Hepatitis B Virus Entry Through Affecting Glycosylated Sodium-Taurocholate Cotransporting Polypeptide Distribution - Hu, Qin; Zhang, Feifei; Duan, Liang; Wang, Bo; Ye, Yuanyuan; Li, Pu; Li, Dandan; Yang, Shengjun; Zhou, Lan; Chen, Weixian (Frontiers in Cellular and Infection Microbiology, 2020)
Hepatitis B virus (HBV) infection is a major cause of chronic liver disease and hepatocellular carcinoma. Current antiviral therapy does not effectively eradicate HBV and further investigations into the mechanisms of viral infection are needed to enable the development of new therapeutic agents. The sodium-taurocholate cotransporting polypeptide (NTCP) has been identified as a functional receptor for HBV entry in liver cells. However, the NTCP receptor is not sufficient for entry and other membrane proteins contribute to modulate HBV entry. This study seeks to understand how the NTCP functions in HBV entry. Herein we show that knockdown of the cell-cell adhesion molecule, E-cadherin significantly reduced infection by HBV particles and entry by HBV pseudoparticles in infected liver cells and cell lines. The glycosylated NTCP localizes to the plasma membrane through interaction with E- cadherin, which increases interaction with the preS1 portion of the Large HBV surface antigen. Our study contributes novel insights that advance knowledge of HBV infection at the level of host cell binding and viral entry.